2009
DOI: 10.1038/tpj.2009.42
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of nicotine-exposed cells from the brainstem of neonate spontaneously hypertensive and Wistar Kyoto rats

Abstract: In this study, the effects of nicotine on global gene expression of cultured cells from the brainstem of spontaneously hypertensive rat (SHR) and normotensive Wistar Kyoto (WKY) rats were evaluated using whole-genome oligoarrays. We found that nicotine may act differentially on the gene expression profiles of SHR and WKY. The influence of strain was present in 321 genes that were differentially expressed in SHR as compared with WKY brainstem cells independently of the nicotine treatment. A total of 146 genes h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…The identification of neuropeptide and neurotransmitter systems is supported by work done in adult male SD, WKY, and SHR rats, as prolactin receptor, neuropeptide Y1 and Y5 receptors, glucagon-like peptide-1 receptor, cannabinoid 1 receptor, and adiponectin receptor are involved in HTN (25). In addition, following nicotine treatment, transcriptomics in the brain stem of WKY and SHR showed that animals may respond differently in the brain stem and involve cellular pathways related to neurotransmitter secretion and intracellular trafficking (16). Thus, the meta-analyses supports the notion that neuro-hormone transcripts related to feeding are associated with HTN.…”
Section: Murine Data Suggest That Gut-brain Neuropeptides Are Associated With Neurogenic Htnmentioning
confidence: 97%
“…The identification of neuropeptide and neurotransmitter systems is supported by work done in adult male SD, WKY, and SHR rats, as prolactin receptor, neuropeptide Y1 and Y5 receptors, glucagon-like peptide-1 receptor, cannabinoid 1 receptor, and adiponectin receptor are involved in HTN (25). In addition, following nicotine treatment, transcriptomics in the brain stem of WKY and SHR showed that animals may respond differently in the brain stem and involve cellular pathways related to neurotransmitter secretion and intracellular trafficking (16). Thus, the meta-analyses supports the notion that neuro-hormone transcripts related to feeding are associated with HTN.…”
Section: Murine Data Suggest That Gut-brain Neuropeptides Are Associated With Neurogenic Htnmentioning
confidence: 97%